Self-efficacy beliefs of English teachers from a non-educational background in the Indonesian context - Noviani, Stella; Kuswandono, Paulus (Englisia: Journal of Language, Education, and Humanities, 2022)
This research investigates how English teachers with a non-English educational background demonstrate their self-efficacy beliefs on the technological pedagogical content knowledge (TPACK) toward their professional practices. The data was obtained from 18 teachers from a non-English educational background in formal and informal Indonesian education settings. Those teachers undertook strategies to develop the technological pedagogical content knowledge (TPACK) while managing their self-efficacy beliefs. Employing a mixed-method research approach, this study gathered the data using closed-ended and open-ended questionnaires, individual interviews, and in-depth interviews. Responses revealed that 18 participants completed a 5-item Likert-type survey measuring the level of teachers’ TPACK self-efficacy. The survey measures the three major aspects of TPACK mean value for teachers’ technological knowledge (TK) (X ̅=23.55) and pedagogical knowledge (PK) (X ̅=19.55), both of which are relatively higher than the value of the content knowledge (CK) (X ̅=16). The dominant factor affecting the high percentage in those two aspects emanates from the teachers’ persistent accounts that they need to be independent in learning while constantly updating their knowledge. This research also discusses the suggestion for future research studies for developing teachers’ TPACK self-efficacy.